2011
DOI: 10.1590/s0034-89102011005000071
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de um escore clínico para rastreamento de suspeitos de tuberculose pulmonar

Abstract: OBJECTIVE:To assess the accuracy (sensitivity) of a clinical score for presumptive pulmonary tuberculosis cases during screening. METHODS:Descriptive cross-sectional study comprising 1,365 patients attending the department of lung diseases at a secondary care outpatient clinic in the city of Rio de Janeiro, Southeastern Brazil, during 2006 and 2007. All respondents answered a standardized questionnaire administered by the clinic's nursing staff. Information on age, weight and clinical symptoms were collected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 9 publications
0
7
0
8
Order By: Relevance
“…Initially all volunteering HCWs were administered a TB symptom screening questionnaire [23] with symptomless HCWs being administered a second questionnaire collecting information on individual, occupational and administrative risk factors. This questionnaire of closed ended questions was designed using the TB risk assessment worksheet from United States Centers for Disease Control and Prevention (CDC) [24], validated and corrected in a pilot study.…”
Section: Methodsmentioning
confidence: 99%
“…Initially all volunteering HCWs were administered a TB symptom screening questionnaire [23] with symptomless HCWs being administered a second questionnaire collecting information on individual, occupational and administrative risk factors. This questionnaire of closed ended questions was designed using the TB risk assessment worksheet from United States Centers for Disease Control and Prevention (CDC) [24], validated and corrected in a pilot study.…”
Section: Methodsmentioning
confidence: 99%
“…Inicialmente, os indivíduos incluídos no estudo responderam a um escore clínico de alta sensibilidade para o diagnóstico presuntivo de TB (9) . Este instrumento é composto por questões de fácil resposta, sem causar constrangimento na entrevista de triagem; sua pontuação varia de zero a 22, o que gera um sistema de escore para a aplicação em pacientes com suspeita de TB.…”
Section: Métodosunclassified
“…Studies selected for analysis in this study showed that nursing staff need to have innovative and efficient tools for patients and their families for early diagnosis (Castro et al, 2011;Silva at al., 2011), as well as effective strategies for monitoring TB treatment (Maciel et al, 2010;Rodrigues et al, 2008).…”
Section: Ijrnmentioning
confidence: 99%